Performance Stability Analysis of Potato Varieties under Rainfed and Irrigated Potato Production Systems in Northwestern Ethiopia - Dessalegn, Y; Mengistu, F; Abebe, T (Ethiopian Journal of Science and Technology, 2025)
In Ethiopia, farmers cultivate potato both in the rainy season under rainfed condition and the dry season using irrigation. Despite the variation in climatic condition and production constraints between the two systems, farmers grow the same variety both in rainfed and irrigated potato production systems. Moreover, researchers release improved varieties only based on performance under rainfed production system. Therefore, the objective of this study was to assess the stability of improved potato varieties across the two potato production systems. Nine potato varieties were evaluated using randomized complete block design with three replications under irrigation and rainfed conditions for two consecutive years at Adet Agricultural Research Center, northwestern Ethiopia. Results revealed that improved varieties performed better in the rainfed production system than the irrigated production system. In addition, there was no stable variety in both production systems. Zengena, CIP384321.3, Genet, Wochecha, Guasa, Tolcha and Menagesha had regression coefficients higher than unity indicating that these varieties prefer favorable condition (rainfed potato production system). The local variety and Awash had regression coefficient less than unity indicating their response to the unfavorable condition (irrigated potato production system). This depicts the relevance of fostering independent variety selection program for each potato production system. However, currently varieties such as Zengena and Guasa can be recommended for both production systems.